Energy Structure and Distribution of Macroscopical Fermion Matter - Syros, C. (HNPS Advances in Nuclear Physics, 2020)
The spatial and energy distribution of fermions are studied in the interior of matter of identical fermions and extremely strong magnetic fields. The vector potential componets are {Ai = 0,1,2,3} periodic in space. The 4-spinor obey the boundary condition Φ=0 at finite distance.